The impact of macroeconomic variables and crude oil price to Bursa Malaysia / Azmer Zul Imman Mohamad Azlan - Mohamad Azlan, Azmer Zul Imman (2022)
The study aims to investigate the effect of macroeconomic variables and crude oil price towards Bursa Malaysia Energy Index. Four independent variables were chosen in conducting the research, namely, Industrial Production, Inflation, Money Supply (M2), and Crude Oil Price. The research utilized 34 monthly observations from the period October 2018 until July 2021. In this research, 3 major tests were conducted, which are descriptive analysis, correlational analysis, and regression analysis. Furthermore, 5 assumption test was conducted to ensure the reliability of the regression result, namely the unit root test, co-integration, serial correlation, heteroscedasticity, and multicollinearity. The unit root test showed all variables were stationary at the first differenced, while the co-integration result showed the existence of long linear relationship between the variables. The research founds 2 variables that give significance impact towards Bursa Malaysia Energy Index, which are Money Supply and Crude Oil Price. Industrial Production and Inflation on the other hand showed nonsignificant impact towards Bursa Malaysia Energy Index. This research provides insight to future researcher and investors on how macroeconomic variables could give impact on oil-sector index in Malaysia and the results may contribute to informed investment decision making.